Implicature Found in The Slogans Of Life Insurance Advertisements - Norra Erisha (English Department, Faculty of Humanities, Andalas University, 2015)
In this research, the writer focuses on the analysis of implicature or implied meaning found in the life insurance’s advertisements published This study is limited on analyzing the advertisement containing pictures. They could be used as the context of the analysis. Therefore, the writer could find out the implicature of the slogans. There are three steps in doing this research; collecting data, analyzing data and presenting the result of data analysis. In collecting the data, 12 slogans of the advertisements were taken from internet. Those data were chosen based on some characteristics. They should have illustrations and pictures in order to help the writer in finding the implicature. Furthermore, the data are analyzed by applying the pragmatics identity method to investigate the data descriptively. The theory used is proposed by Grice and Mey. The finding of the data is presented by using formal and informal method. From the analysis, the writer found some implied meanings in the life insurance slogans. They are related to financial solution, safe and enjoyable life, health protection, solution to future plans, and a great life solution which can be acquired when joining the company of the life insurance. In general, the slogans promote the quality of the company implicitly.Keywords: implicature, context, implied meaning